Limits determination of microbial contamination present on surfaces from a pharmaceutical microbiology district reference laboratory - Natalia Charry; Sandra L. Gómez (GarVal Editorial Ltda., 2016)
Context: The bioburden present on the pharmaceutical microbiology laboratory's surfaces, may increase the risk of cross-contamination when analytical tests are being carried out; periodic monitoring allows to set limits that reduce the risk. Aims: To determinate the limits of bioburden present on seven surfaces of the pharmaceutical microbiology laboratory, after the cleaning and disinfection process. Methods: The swabbing method was used for sampling. With a 25 cm2 stencil and a sterile swab, a sample was taken, passing the swab over five points of every surface chosen. A total aerobic microbial count and a total yeast and mold count was done. Finally, the average and the standard deviation of the counts was obtained. Results: The average from the counts obtained on each surface selected for the study, were below the recommended limits by international entities like the World Health Organization and the European Union, between others; also, the results generated in this study, allow to classify the biosafety cabinet as an ISO 5 area and the other areas as ISO 7. Conclusions: Bioburden levels on the tested surfaces are considered low, reducing the risk of cross-contamination, which could have a negative impact on laboratory's activities. Also, it follows that disinfectant concentration used, is effectively.